Legal Implications Of The Certificate Revocation Decision By The Court Toward The Creditors - Harimurti Kridalaksana; Widiya N. Rosari; Herawan Sauni (Universitas Bengkulu, 2022)
This study aimed to analyze and to explain the legal implications of the court decision which stated that the certificate of ownership was revoked, furthermore it became the mortage right toward the bank as the holder of the mortgage right in the Home Ownership Credit Agreement. The research method used was normative legal research with a statute approach and a case approach. The results of the research showed that with the court's decision, the certificate of ownership rights which became the mortgage rights was no longer legally enforceable, namely 60 (sixty) working days after the court decision has obtained permanent legal force as referred to in Article 116 paragraph (1) of The Administrative Court Law. The decision was accepted if the Defendant did not fulfill his obligations. This also applied regardless of whether or not a revocation request was made to the Head of the local Land Office. Then automatically the mortgage rights also did not have legal force anymore, although this was not regulated in the provisions of the UUHT. However, the credit agreement did not become nullified or canceled, then there was a shift in the position of the bank from the original creditor which was prioritized to be a concurrent creditor.